Climate Change and Sustainable Development: A Collective Approach to Economic Integration in the Islamic World - Arif Zunaidi; Jamaluddin Acmad Kholik; Fachrial Lailatul Maghfiroh; Ana Nur Oktavia Mutamimah; Sintia Rahmawati (IAIN Ponorogo, 2024)
The purpose of this study is to examine the significance of a communal strategy for confronting the global challenge of climate change and fostering sustainable development in the Islamic world. The paper develops a framework for the economic integration of the Islamic world through a review of the literature and case studies of successful countries. The technique employed entails a thorough qualitative examination of pertinent policies, international collaboration, and Islamic principles. The findings show that cross-border collaboration and community empowerment are critical to the Islamic world's economic integration in order to solve climate change. The article also demonstrates how Islamic ideals like amanah, tawhid, and takaful contribute to a community approach to sustainable development. This research has the advantage of providing complete recommendations for Islamic countries and the international community on coping with climate change and fostering sustainable development. The originality of this article lies in its comprehensive approach to economic, environmental, and social issues in the context of the Islamic world. As a result, this paper has the potential to bring fresh perspectives and significance to tackling this critical worldwide issue.